Potential drivers of growth and employment in Mpumalanga province: An assessment of inter-industry linkages using input-output analysis - Sithole, Jabulani Easmouth (My University, 2014)
This study investigates the potential drivers of growth and employment in Mpumalanga’s economy using input-output (I-O) analysis as a contribution to industrial policy research and development for the province. Since 1995 to 2011, the Mpumalanga economy has been dominated by the tertiary sector (Quantec, 2011). Mohamed (2010) argues that in South Africa, while there had been growth in services, this growth has generally not been in productive services but instead has been driven by acceleration in debt-driven consumption, outsourcing and growth in private security services. The unemployment rate in the province was at 30.9 percent and labour absorption 52.0 percent in 2011, which made Mpumulanga the 6th largest contributor to the unemployment rate in the country that year (Quantec, 2011). The fifth iteration of the Industrial Policy Action Plan, 2013/14 – 2015/16 aims to promote a labour absorbing industrialisation path, with the emphasis on the systematic building of economic linkages that create employment. While being aware of potential weaknesses associated with this method, I-O analysis is one of the tools used frequently in the literature for identifying sectors to be supported in the industrial policy. The results of this study shows that the manufacturing sector in the province has a stronger stimulatory power to directly stimulate output in most sectors and drive industrial development, provided that local imports and available skills can be used appropriately to fill the existing gaps. This study forms the basis for the Mpumalanga Province’s policymakers to further conduct sector analysis through other refined supplementary methods such as value chain analysis with the purpose to confirm linkages of the sectors and determine key sectors that have the potential to drive industrialisation in the province.
Keywords: Economic development; South Africa; Mpumalanga; Economic policy; Input-output analysis